Characteristics of Hybrid Nanolubricants for MQL Cooling lubrication machining application - Syh Kai, Lim; Wan Hamzah, Azmi; Ahmad Shahir, Jamaludin; Ahmad Razlan, Yusoff (MDPI, 2022)
Efficient and effective lubricants have great application prospects in the manufacturing industries. Minimum quantity lubrication (MQL) machining with low flow rate of nanolubricants is investigated for cooling and lubrication during the process. This paper investigates the characterization of graphene-mixed aluminium oxide (G-Al2O3 ) hybrid nanomixture spent lubricants for MQL machining purposes. The main advantage of this method is to reduce the disposal lubricants to develop high-performance cooling-lubrication by using nanolubricants of G-Al2O3 nanoparticles in different volume composition ratios at a constant 1.0% volume concentration in a base liquid mixture of 40% spent lubricants. Before conducting the measurements of the nanolubricants’ thermal conductivity and dynamic viscosity, the nanolubricants were homogenous and stable. The tribological performance of all ratios was evaluated by using a four-ball wear tribotester machine. The thermal conductivity peak value for the G-Al2O3 hybrid nanolubricant was obtained and the highest enhancement, up to 29% higher than the base liquid solution, was obtained. The dynamic viscosity variation for all ratios was lower than the 40:60 ratio. The properties enhancement ratio suggests that G-Al2O3 hybrid nanolubricants with 1.0% volume concentration aid in the heat transfer, especially for ratios of 60:40 and 20:80. The lowest coefficient of friction (COF) for a ratio of 60:40 was obtained to be 0.064, with 45% enhancement as compared to the base liquid solution. In conclusion, optimum ratios for G-Al2O3 hybrid nanolubricants were determined to be 20:80 and 60:40. Regarding the properties enhancement ratio, the combination of enhanced thermophysical and tribological properties had more advantages for cooling lubrication application.